Pengaruh Pemberian Berbagai Dosis Kurkuminoid terhadap Kecernaan Protein, Efisiensi Protein dan Kecepatan Laju Makanan dalam Sistem Pencernaan Babi Finisher - Sinaga, Sauland; Silalahi, Marsudin (Politeknik Negeri Lampung., 2011)
The research on The Effect of Providing Curcuminoid Dosage To Digestible protein, Protein Efficiency and The Rate of Passage of Feed in Grower Period Pig?s Digest System has been conducted since January 10th, to 27thFebruary 2008, at Pig Livestock Laboratory and Teaching Farm of KPBI Obor Swastika in Cisarua, Bandung, Indonesia. The aim of this research was to state the effect of providing and the best dosage of curcuminoid in meal to digestible protein, protein efficiency and the rate of passage of feed in grower period pig?s digest system. This research used 20 grower period pigs with 35 kg average body weight and 2,13 percent variation coefficient. The experiment used the completely randomized design, the treatment given was the addition level of curcuminoid dosage (0, 4, 8 and 12 mg curcuminoid/kg body weight). Each treatment was done five times. The result of this research gives 4 mg curcuminoid/kg body weight give in ration finisher pig increase protein digestability and no significant for protein efficiency and passing rate feed Keywords : Curcuminoid, Digestible Protein, Protein Efficiency, Rate of Passage of Meal in Digest System, Grower Period Pig